Development of thermal and deformation stability of Qinghai-Tibet Highway under sunny-shady slope effect in southern Tanglha region in recent decade - Song, Y; Jin, L; Peng, H; Liu, H (Soils and Foundations, 2020)
The Qinghai-Tibet Highway (QTH) crosses 528 km of a permafrost region in the Qinghai-Tibet Plateau, half of which has suffered freezing-thawing damage induced by the sunny-shady slope effect (SSSE), especially in the Southern Tanglha Region (STR). Given this problem, a continual field investigation was carried out in the STR to examine the types of damage and the development characteristics of the affected embankments. The investigation indicated that up to 60% of the damage featured an asymmetric specialty, mainly comprising uneven thaw deformation and longitudinal cracks. Furthermore, the long-term monitoring data taken from four observation sites in a recent decade, including the shallow soil temperature, ground temperature, freezing-thawing processes, and deformation, were used to analyze the thermal-deformation process of the embankments as well. Under the SSSE, the temperature fields of the embankments were characterized by the increase in ground temperature, the descent of the permafrost table, and the expansion of the thawing period in the sunny slopes during the operation period, representing several remarkable asymmetric phenomena. Specifically, the maximum difference between the annual average shallow soil temperatures of the sunny and shady slopes reached 3.17 C. In addition, the permafrost table on the sunny slope side was about 1.0 m lower than that on the shady slope side because the thawing period is 12 months longer each year on the sunny slope side. Correspondingly, the asymmetric thermal state of the embankments led to varying degrees of asymmetric deformations. The heat budget calculation showed that the route direction was the most significant factor of influence on the SSSE. The embankment height was also seen to have a remarkable influence on the SSSE.